Methods for hemicellulose deconstruction aiming to xylose recovery: Recent progress and future perspectives - Almeida, Sâmilla G. C. [UNESP]; Silva, Veronica T. F.; Souza, Jonas P. [UNESP]; Prado, Cleiton D.; Oliveira, Débora K. S. [UNESP]; Silva, Débora D. V. [UNESP]; Dussán, Kelly J. [UNESP] (My University, 2022)
Lignocellulosic biomass currently represents the most significant potential to produce biofuels and biochemical compounds because of its abundance and cost savings. For using these materials, pretreatment is one of the essential steps in the biomass conversion process. However, the physical and chemical barriers from the main constituents (cellulose, hemicellulose, lignin) and their interactions form a hardheaded structure, creating a barrier to recover the fermentable sugars. Hemicellulose hydrolysis results in a xylose-rich hydrolysate that can be converted to high add-value chemicals, like xylitol. Each type of pretreatment will affect most downstream processes and represent a portion of the costs of the bioprocess. In this way, the selection of one pretreatment cost-effective and viable is a significant challenge. Moreover, each specific pretreatment will act differently in the lignocellulosic matrix; therefore, the choice must consider the configuration of the process used and the characteristics of the subsequent fermentation. This chapter aims to provide an overview and critically about hemicellulose deconstruction techniques aiming at xylose recovery, approach the perspectives, and show promising methods for disrupting the lignocellulosic matrix.
Keywords: Fermentation; Lignocellulosic biomass; Pretreatment; Xylitol